2017
DOI: 10.1111/adj.12531
|View full text |Cite
|
Sign up to set email alerts
|

Does early‐life family income influence later dental pain experience? A prospective 14‐year study

Abstract: Early-life relative poverty is associated with more frequent dental pain across the 14-year follow up and may be a key exposure variable for later dental conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
1
15
1
Order By: Relevance
“…This study found that in the late phase of mixed dentition, children age 9-12, reported less frequent toothache experience than the previous age period (12%). This result was lower than a study in South Brazil for children 8-12 years that reported toothache experience for 17.3% of the population 29 and a study for children age 9-12 years in Australia (27.4%) 12 . This number is also lower than a study in Taiwan where more than 30% of children experience dental pain during the past year 15 .…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…This study found that in the late phase of mixed dentition, children age 9-12, reported less frequent toothache experience than the previous age period (12%). This result was lower than a study in South Brazil for children 8-12 years that reported toothache experience for 17.3% of the population 29 and a study for children age 9-12 years in Australia (27.4%) 12 . This number is also lower than a study in Taiwan where more than 30% of children experience dental pain during the past year 15 .…”
Section: Discussioncontrasting
confidence: 66%
“…Understanding the sequences of toothache experience in a lifetime is crucial to prevent toothache in an appropriate period of life. The individual life-course approach to diseases is the critical period of development, which presumes that having experience of certain conditions in early life can have long term impacts on later health outcomes 12 . We may understand that people in certain periods of life experience a higher rate of toothache in their life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,4 In Brazil, caries experience increases from 43.5% to 76.1% during adolescence, affecting 99% of Brazilians aged 35 to 44 years, 5 and dental caries is strongly associated with dental pain. Moreover, dental pain has been associated with loss of work productivity, school absenteeism, difficulty sleeping, refusal to eat certain foods, and greater use of healthcare services, 1,2,3,[6][7][8][9] which often Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%